2016
DOI: 10.1111/gcb.13571
|View full text |Cite
|
Sign up to set email alerts
|

A near half‐century of temporal change in different facets of avian diversity

Abstract: Assessments of spatial patterns of biodiversity change are essential to detect a signature of anthropogenic impacts, inform monitoring and conservation programs, and evaluate implications of biodiversity loss to humans. While taxonomic diversity (TD) is the most commonly assessed attribute of biodiversity, it misses the potential functional or phylogenetic implications of species losses or gains for ecosystems. Functional diversity (FD) and phylogenetic diversity (PD) are able to capture these important trait-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 109 publications
7
102
1
1
Order By: Relevance
“…We documented a positive association between temperature and beta diversity for all dimensions, but we found lower phylogenetic and functional diversity in topographically diverse regions (Figure ). This result echoes the temporal pattern documented by Jarzyna and Jetz (), suggesting that bird communities at high elevations and in cold regions might be relatively homogeneous and thus relatively more vulnerable to changing climate. In the case of breeding birds in the USA, topographically diverse regions might, in fact, be the most sensitive to environmental change.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We documented a positive association between temperature and beta diversity for all dimensions, but we found lower phylogenetic and functional diversity in topographically diverse regions (Figure ). This result echoes the temporal pattern documented by Jarzyna and Jetz (), suggesting that bird communities at high elevations and in cold regions might be relatively homogeneous and thus relatively more vulnerable to changing climate. In the case of breeding birds in the USA, topographically diverse regions might, in fact, be the most sensitive to environmental change.…”
Section: Discussionsupporting
confidence: 87%
“…Although our study does not address change over time, the discrepancy between taxonomic and functional/phylogenetic diversity patterns with topographical variability and with temperature is notable. Jarzyna and Jetz () also observed that the greatest temporal changes in diversity occurred at higher elevations and latitudes, ascribing this pattern to climate change. We documented a positive association between temperature and beta diversity for all dimensions, but we found lower phylogenetic and functional diversity in topographically diverse regions (Figure ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…To assess the congruence between changes in taxonomic, functional, and phylogenetic aspects at both alpha and beta diversity levels, we used a permutation procedure with 999 iterations to test the difference in slopes between the regression line of any two changes and the 1:1 line. In addition, we disentangled the cross‐associations of changes in TD, FD, and PD ([agricultural diversity − natural diversity]/natural diversity) or similarity (agricultural similarity − natural similarity) into different scenarios to gain a better understanding of the underlying processes of biodiversity changes (Figure ; Baiser & Lockwood, ; Jarzyna & Jetz, ). For example, a larger increase in TD compared to the increase in FD (or PD) could come from a gain in functionally (or phylogenetically) redundant taxa (Figure a, region II); while a larger increase in FD (or PD) could be explained by a gain in functionally (or phylogenetically) distinct taxa (Figure a, region I; Jarzyna & Jetz, ).…”
Section: Methodsmentioning
confidence: 99%
“…Integrated measurement of TD, PD, and FD can provide a comprehensive representation of biodiversity patterns and ecological functions (Calba, Maris, & Devictor, 2014;Pollock et al, 2017). This approach has been applied to the mapping of global biodiversity patterns of certain taxa (Safi et al, 2011), elucidating linkages between biodiversity and ecosystem functions and services (Cadotte, Dinnage, & Tilman, 2012;Flynn et al, 2009;Jarzyna & Jetz, 2017) for conservation policy (Pollock et al, 2017), and to provide insights on how ecological communities are shaped by evolutionary history and the environment (Calba et al, 2014;Jarzyna & Jetz, 2017;Ricklefs, 2007). For example, a community with high PD relative to TD indicates phylogenetic overdispersion; the community consists of mostly unrelated lineages, perhaps due to competitive exclusion as a long history of competitive interactions can cause evolutionary divergence in species niches (Violle, Nemergut, Pu, & Jiang, 2011).…”
Section: Introductionmentioning
confidence: 99%